Measuring the Root Length of Peanuts Grown in Rhizotrons Using Computer Vision - Stefanello, Leonardo Michalski; Silva, Leonardo Paillo da; Dayrell, Luís Henrique Soares; Ferrari Neto, Jayme; Pistori, Hemerson; Nucci, Higor Henrique Picoli (Anais do Workshop de Visão Computacional (WVC), 2021)
Peanut is one of the most grown leguminous crops in the world, but it can suffer during water deficit periods. In this paper, a new method to help monitoring root growth for laboratory experiments with this plant is proposed. By using a new combination of smoothing, thresholding, morphological filtering and skeletonization, our method has achieved a correlation of 0.968 with the Tennant's standard approach.